Human-In-The-Loop Control and Task Learning for Pneumatically Actuated Muscle Based Robots - Teramae, Tatsuya; Ishihara, Koji; Babič, Jan; Morimoto, Jun; Oztop, Erhan (Frontiers in Neurorobotics, 2018)
Pneumatically actuated muscles provide a low cost, lightweight and high power-to-weight ratio solution for many robotic applications. In addition, the antagonist pair configuration for robotic arms make it open to biologically inspired control approaches. In spite of these advantages, they have not been widely adopted in human-in-the-loop control and learning applications. In this study, we propose a biologically inspired multimodal human-in-the-loop control system for driving a one degree-of-freedom robot, and realize the task of hammering a nail into a wood block under human control. We analyze the human sensorimotor learning in this system through a set of experiments, and show that effective autonomous hammering skill can be readily obtained through the developed human-robot interface. The results indicate that a human-in-the-loop learning setup with anthropomorphically valid multi-modal human-robot interface leads to fast learning, thus can be used to effectively derive autonomous robot skills for ballistic motor tasks that require continuous modulation of impedance.